2018
DOI: 10.1007/s00421-018-3801-7
|View full text |Cite
|
Sign up to set email alerts
|

Sodium bicarbonate supplementation improves severe-intensity intermittent exercise under moderate acute hypoxic conditions

Abstract: Acute moderate hypoxic exposure can substantially impair exercise performance, which occurs with a concurrent exacerbated rise in hydrogen cation (H+) production. The purpose of this study was therefore, to alleviate this acidic stress through sodium bicarbonate (NaHCO3) supplementation and determine the corresponding effects on severe-intensity intermittent exercise performance. Eleven recreationally active individuals participated in this randomised, double-blind, crossover study performed under acute normob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 46 publications
(67 reference statements)
4
37
1
1
Order By: Relevance
“…The primary finding of the study was that chronic NaHCO 3 ingestion had a considerable impact on acid-base balance, which resulted in a higher alkalotic state; however, chronic NaHCO 3 ingestion did not significantly influence PTSR-related performance outputs and associated physiological responses. A higher alkalotic acid-base balance prior to exercise under hypoxic conditions has been reported to be related to higher performance output and higher maximum blood lactate values after highintensity exercise [11,16,19]. The suggested mechanism underlying the increased [H + ] buffering from intramuscular to extramuscular compartments may lead to improved protection of intramuscular pH and increased anaerobic energy provision and glycogen utilization [16,50].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The primary finding of the study was that chronic NaHCO 3 ingestion had a considerable impact on acid-base balance, which resulted in a higher alkalotic state; however, chronic NaHCO 3 ingestion did not significantly influence PTSR-related performance outputs and associated physiological responses. A higher alkalotic acid-base balance prior to exercise under hypoxic conditions has been reported to be related to higher performance output and higher maximum blood lactate values after highintensity exercise [11,16,19]. The suggested mechanism underlying the increased [H + ] buffering from intramuscular to extramuscular compartments may lead to improved protection of intramuscular pH and increased anaerobic energy provision and glycogen utilization [16,50].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies reported increased or constant anaerobic exercise performance during acute altitude exposure in hypoxic chambers following supplementation with alkalizing agents prior to exercise [11,16,19,[22][23][24]. All these studies analyzed the effects of bicarbonate supplementation on different aspects of exercise performance under acute hypoxic conditions (between 15 min and 4 h of altitude exposure).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations